Prostitution, identity and the Neo-Victorian: Sarah Waters’ tipping the Velvet and the Ripper Street Series. - Romero-Ruiz, María Isabel (My University, 2014)
The analysis of sexual abuse and violence in two Neo-Victorian literary and visual productions, Sarah Waters’ Tipping the Velvet (1999) and the BBC’s drama series Ripper Street (2012) will be the object of discussion in terms of agency of and mourning for the abused. Tipping the Velvet is set in the last decades of the nineteenth century and its two lesbian protagonists are given voice as the marginalised and the other, following the Neo-Victorian trend of re-writing the history of those whose lives were not found in the mainstream historical record. Judith Butler’s notion of gender performance is taken to its extremes in a story where male prostitution is exerted through a woman who behaves and dresses like a man, but who will also become the victim of sexual violence and abuse. In Ripper Street, the protagonist, the leader of the Whitechapel H Division, Inspector Edmund Reid, tries to do justice to the women who sell their bodies in London East End in 1889 after the Ripper’s murders. Their aim is not only to keep order in this working-class suburb, but also to find the way to show sympathy for the deaths and suffering of the “prostituted other”. Therefore, drawing from Butler’s theories of gender, violence and mourning, this paper will address Victorian and contemporary discourses connected with the notions of sexual identity and agency as the result of sexual violence and gender abuse, and of the prostituted body as the site of vulnerability and dependency of “the other”.
Keywords: Novela negra; Prostitution; Identity; Neo-Victorian; Ripper Street; Sarah Waters